Artificial Intelligence for Drug Discovery and Environmental Sciences - Mukhopadhyay, Supratik; Chris, Alvin; Adam, Bess (Proceedings of the International Florida Artificial Intelligence Research Society Conference, 2025)
Addressing global health challenges and environmental threats requires innovative technological solutions.Despite advances in medicine, millions suffer from conditions lacking effective treatments, while antibiotic resistance grows and traditional drug development pipeline remains slow and costly.DeepDrug, our AI-powered drug design pipeline, accelerate therapeutic discovery by efficiently analyzing vast datasets to identify promising compounds.Simultaneously, climate change manifests through increasing natural disasters, pollution, habitat destruction, and agricultural disruption, threatening both human civilization and biodiversity.Our research demonstrates how artificial intelligence can address these dual challenges through advanced data analysis, predictive modeling, and decision support systems.We present applications ranging from drug discovery to environmental monitoring, including understanding satellite imagery, wildfire management, and predicting permafrost changes.